Pelatihan Kader Perencanaan Sehat sebagai Penggerak Edukasi Pra-Konsepsi di Dusun Olat Rarang Desa Labuhan Sumbawa - Fitri Setianingsih; Ninik Wahyuni; Galuh Permatasari; Nurlaila Agustikawati (Institut Nalanda, 2026)
Pre-conception health planning is essential for maternal and child health quality, yet public awareness in rural areas remains low. This community service aims to establish and optimize the role of the